Dielectric Polymer Nanocomposites - Nelson, J. Keith; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Dielectric Polymer Nanocomposites provides the first in-depth discussion of nano-dielectrics, an emerging and fast moving topic in electrical insulation. The book provides an overview of the background, principles and promise of nanodielectrics, as well as a discussion of the processing of nanocomposites. Special considerations are also given to clay based processes, mechanical, thermal and electric properties and surface properties, as well as erosion resistance. Carbon nanotubes are discussed as a means of creation of nonlinear conductivity. Editor J. Keith Nelson brings together the leading minds in the field, whose contributions to the book also: Discusses the background, principles and importance of nano-dielectric composites Includes complete coverage of nanodielectric composites such as cryogenic applications, high voltage stress grading materials and applications in the capacitor industry Provides detailed coverage on the processing of nanocomposites Dielectric Polymer Nanocomposites is perfect for academics and researchers working in or interested in learning more about this growing field. .
Background, Principles and Promise of Nanodielectrics -- The Processing of Nanocomposites -- Special Considerations for Clay-Based Materials -- The Chemistry and Physics of the Interface Region and Functionalization -- Modeling the Physics and Chemistry of Interfaces in Nanodielectrics -- Mechanical and Thermal Properties -- Electrical Properties -- Interface Properties and Surface Erosion Resistance -- Non-linear Field Grading Materials and Carbon Nanotube Nanocomposites with Controlled Conductivity -- The Emerging Mechanistic Picture -- Industrial Applications Perspective of Nanodielectrics.
Keywords: Engineering; Polymers .; Electronics; Microelectronics; Optical materials; Electronic materials; Ceramics; Glass; Composites (Materials).; Composite materials; Nanotechnology; Engineering, general; Polymer Sciences; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Ceramics, Glass, Composites, Natural Materials; Nanotechnology